Break or weld? trade union responses to global value chain restructuring. (1st April 2008) - Ursula Huws,
Abstract : This paper provides a short introduction to this volume, sketching out some of the main dilemmas confronting trade unions in the context of global value chain restructuring, discussing some of the alternative strategies currently being adopted around the world and summarising the contributions to this volume.